The correlation between psychosocial characteristics and psychiatric hospital admission rates of patients with paranoid schizophrenia - V. E. Pashkovskiy; A. G. Sofronov; I. D. Fedorovskiy; L. G. Serasetdinova; I. V. Lemeshev; A. E. Dobrovolskaya (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
To identify the correlation between psychosocial characteristics of patients with paranoid schizophrenia placed under medical supervision and rates of their admissions to psychiatric hospitals, 80 patients (50 men and 30 women) aged 42,8±10.9 years have been studied. The results showed that psychosocial characteristics such as age, level of education attained, having a job and work experience, financial and marital statuses and social circle latitude were in inversely proportional relationship with the rate of hospital admissions. Multiple regression analysis showed the duration of disease and social circle latitude to be the most important predictors of the frequency of hospital admissions. The obtained results indicate that reduction in hospital admission numbers can be achieved by providing the patient with the combination of medical, psychosocial and family therapies, as well as employment assistance and rehabilitation of communication skills.